2013
DOI: 10.1021/bi401125v
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Mediated Conformational Changes in the Steroidogenic Acute Regulatory Protein Are Essential for Steroidogenesis

Abstract: Although the mechanism by which the steroidogenic acute regulatory protein (StAR) promotes steroidogenesis has been studied extensively, it remains incompletely characterized. Because structural analysis has revealed a hydrophobic sterol-binding pocket (SBP) within StAR, this study sought to examine the regulatory role of cholesterol concentrations on protein folding and mitochondrial import. Stopped-flow analyses revealed that at low concentrations, cholesterol promotes StAR folding. With increasing cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 68 publications
2
27
0
1
Order By: Relevance
“…StAR phosphorylation by PKA is neither necessary nor dependent on the presence of cholesterol in the reaction media (Baker et al, 2007), in agreement with our observations (Poderoso et al, 2008). This result indicates that StAR phosphorylation by kinases other than PKA is modulated by the endogenous ligand of the protein, in agreement with recent work showing that cholesterol is a potent activator of StAR metabolism (Rajapaksha et al, 2013).…”
Section: Functional Phosphorylation Of Star By Pka and Erksupporting
confidence: 92%
“…StAR phosphorylation by PKA is neither necessary nor dependent on the presence of cholesterol in the reaction media (Baker et al, 2007), in agreement with our observations (Poderoso et al, 2008). This result indicates that StAR phosphorylation by kinases other than PKA is modulated by the endogenous ligand of the protein, in agreement with recent work showing that cholesterol is a potent activator of StAR metabolism (Rajapaksha et al, 2013).…”
Section: Functional Phosphorylation Of Star By Pka and Erksupporting
confidence: 92%
“…Mitochondria-StAR import is slower than that observed for other mitochondrial targeting sequences (18), and it competes only with its own N-terminal sequence (38); however, the impact of the N-terminal sequence is unknown. Therefore, we constructed a recombinant StAR in which 30 amino acids of the N-terminal StAR sequence were substituted with the P450scc mitochondrial sequence (SCC/StAR) and determined whether it still transits through the MAM fraction.…”
Section: Specificity Of Star Targeting From the Mam To Thementioning
confidence: 87%
“…Under stress, the flux of cholesterol changes dramatically due to enhanced hydrolysis of stored cholesterol esters, increased uptake of plasma cholesterol, and transport of free cholesterol into the mitochondria for the synthesis of steroid hormones in response to ACTH. Free cholesterol induces tighter StAR folding; however, excess cholesterol results in the unfolding of StAR (38). Thus, in the presence of excess cholesterol, StAR may possibly remain associated with the other MAM proteins, and after most of the cholesterol pool is imported into the mitochondria, the remaining cholesterol may promote StAR refolding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described (Rajapaksha et al, 2011(Rajapaksha et al, , 2013a, hydrophilicity analysis has shown that the N-terminal 3bHSD2 sequence is more hydrophobic up to amino acid 120, and the amino acid sequence of the rest of the protein is weakly hydrophobic and does not form an amphiphilic helix, resulting in a favored association with the membrane. The association may be the result of an electrostatic interaction between the positively charged residues of the C terminus of the protein and the less polar cortisone and androstenedione.…”
Section: Discussionmentioning
confidence: 66%